Risk Perception and Return Expectation on Investment Decisions in the Capital Market - Diendra Kusuma Warjono; Maretha Ika Prajawati; Muhammad Sulhan (Universitas Negeri Padang, 2024)
This study examines the effects of risk perception and return expectations on investment decision-making among students in the capital market context. Using a quantitative approach, the population comprises 520 active students from the Faculty of Economics at UIN Maulana Malik Ibrahim Malang. A sample of 84 respondents was selected through simple random sampling by employing Slovin’s formula to ensure equal selection opportunity and representativeness. Data collection involves structured questionnaires measuring risk perception, return expectations, and investment decisions. Investment decisions serve as the dependent variable, while risk perception and return expectations are independent variables. The indicators for each variable align with foundational theories to capture their essential dimensions, ensuring data relevance and accuracy. Data analysis was performed using SPSS 27, incorporating descriptive statistics to summarize respondent demographics and regression analysis to evaluate variable influences. The findings reveal that risk perception and return expectations significantly and positively affect students’ investment decisions. This suggests that students consider both risk and potential returns, reflecting a sound understanding of investment principles before making decisions